Response of Pollen and Productivity of Rice Plants to the Application of Salicylic Acid under Drought Stress - Ika Purnamasari; Balqis Widyastuti Suparino; Angger Aisyah Hadiahning Gusti; Rosalina Diva Aurela; Yagus Wijayanto; Agung Nugroho Puspito; Mohammad Ubaidillah (Institut Pertanian Bogor, 2025)
Rice plants (Oryza sativa) are among the most significant food crops in human life. Efforts to increase food production face a variety of challenges, including droughts. Drought stress is abiotic stress that has a significant impact on rice plant growth and development. Plants treated with salicylic acid are more resistant to water shortage. Salicylic acid influences plant growth in terms of weight, height, and grain yield. The use of salicylic acid may increase the weight of plant seedlings. The purpose of this study was to determine how rice plant productivity responds to the addition of salicylic acid during drought stress. The study was carried out in a greenhouse from August to December 2020 utilizing a Completely Randomized Design with two variables: plant variety and drought stress. The cultivars used were Indragiri, Mendawak, and IR64. The drought treatment factors were control, drought stress, and drought stress treated with salicylic acid. There were nine treatment combinations and three replications, totaling 27 experimental units. The data collected were analyzed using Analysis of Variance. If significant differences were discovered, the analysis was extended with Duncan's Multiple Range Test at a 95% confidence level. The findings revealed that both individual factors and their interactions had a substantial influence on various variables. The interaction factor had a substantial impact on pollen fertility, panicle length, number of full grains, weight per 1,000 grains, and yield potential. The rice variety had a substantial effect on pollen fertility, panicle length, number of filled grains, and yield potential, but not on the weight of 1000-grains. Keywords: drought stress, rice, salicylic acid